Effectiveness of the 2010 and 2011 Southern Hemisphere trivalent inactivated influenza vaccines against hospitalization with influenza‐associated acute respiratory infection among Thai adults aged ≥50 years. Issue 4 (3rd February 2014) - Dawood, Fatimah S.; Prapasiri, Prabda; Areerat, Peera; Ruayajin, Asadang; Chittaganpitch, Malinee; Muangchana, Charung; Baggett, Henry C.; Olsen, Sonja J.
<x xml:space="preserve">Abstract</x> Background Inactivated influenza vaccine (IIV) effectiveness has been evaluated among older adults in high‐income countries, but data on IIV effectiveness in low‐ and middle‐income countries remain sparse. We conducted a test‐negative case–control analysis to estimate 2010 and 2011 trivalent IIV effectiveness against hospitalization with influenza‐associated acute respiratory infection (ARI) among persons aged ≥50 years in rural Thailand. Methods During 2010–2011, active surveillance for ARI hospitalization was conducted in two provinces; patients were tested for influenza viruses by real‐time RT‐PCR. Vaccination status was obtained from vaccine registries. Case and control patients were patients with nasopharyngeal swabs positive and negative for influenza viruses, respectively. Vaccine effectiveness (VE) was estimated for the 6 months after vaccination began. Logistic regression was used to evaluate the association between case status and vaccination while adjusting for age, province, medical conditions, and time. Results During 2010–2011, there were 1545 patients with ARI, of whom 279 (18%) were influenza‐positive case patients and 1266 (82%) were influenza‐negative control patients. Of the 279 case patients, 247 (89%) had influenza A and 32 (11%) had influenza B. Fourteen of 279 (5%) case patients and 108 of 1266 (9%) control patients were vaccinated against influenza. The unadjusted IIV effectiveness against hospitalization with influenza‐associated ARI was 43% (95% CI: 0–68%); adjusted VE was 47% (95% CI: 5–71%). Conclusion The 2010 and 2011 IIVs were moderately effective against hospitalization with influenza‐associated ARI among Thais aged ≥50 years, but IIV coverage was low. Additional efforts are warranted in Thailand to improve IIV uptake in this target group.